2012
DOI: 10.1186/1472-6963-12-302
|View full text |Cite
|
Sign up to set email alerts
|

Growing old before growing rich: inequality in health service utilization among the mid-aged and elderly in Gansu and Zhejiang Provinces, China

Abstract: BackgroundChina’s recent growth in income has been unequally distributed, resulting in an unusually rapid retreat from relative income equality, which has impacted negatively on health services access. There exists a significant gap between health care utilization in rural and urban areas and inequality in health care access due to differences in socioeconomic status is increasing. We investigate inequality in service utilization among the mid-aged and elderly, with a special attention of health insurance.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
95
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 31 publications
(30 reference statements)
9
95
1
Order By: Relevance
“…This is a trade-off between sample size and comparability and we believe the latter matters the most. The final sample size of this study is similar to previously published studies [14,31]. Secondly, although the insured and uninsured residents have been matched before comparing their health utilisation equity, since this is not an experimental study, we cannot control the unobservable characteristics (such as risk attitude and personality), the casual relationship cannot be attained by this study.…”
Section: Discussionmentioning
confidence: 93%
“…This is a trade-off between sample size and comparability and we believe the latter matters the most. The final sample size of this study is similar to previously published studies [14,31]. Secondly, although the insured and uninsured residents have been matched before comparing their health utilisation equity, since this is not an experimental study, we cannot control the unobservable characteristics (such as risk attitude and personality), the casual relationship cannot be attained by this study.…”
Section: Discussionmentioning
confidence: 93%
“…Zhou et al [16] suggested that inpatient care use was concentrated among the better-off, but the inequity indices decreased from 0.224 in 2003 to 0.115 in 2008. In terms of outpatient care use for mid-aged and elderly people, Wang et al [15] found that in more affluent provinces like Zhejiang, outpatient use was concentrated among the better-off, while in provinces with low economic development, such as Gansu, use of health care was equally distributed across income groups. The study also suggested that this may be because of the difference in terms of health care provision and coverage of insurance between these two provinces.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies either limit their investigations to a given point in time [15,17,19], or a specific health service [16]. The NCMS has been implemented for a few years, but it is still not clear if the scheme has any impact on utilisation.…”
Section: Introductionmentioning
confidence: 99%
“…This age group can be more vulnerable to illness conditions and in more need of health insurance protection [18]. Samples of the existing studies have been randomly selected, covering the majority of municipalities and provinces in mainland China.…”
Section: Methodsmentioning
confidence: 99%